The relationship between learning capability and organizational performance: the banking sector in Greece - Therios, Georgios N. (SPOUDAI Journal of Economics and Business, 2007)
This study, examines the concept of the Learning Organizations in the Greek banking sector based on ‘learning capability’, organization factors (size and formalization) and performance measures. From the analysis of the results it is shown, that the five managerial practices, necessary for organizational learning, are used on the Greek banking sector at satisfactory levels. Concerning the relationship of the learning capability with performance, the results of this study show that ‘learning capability’ definitely affects positively the firm’s performance, especially the non-financial measure of job satisfaction but also ROA. As far as the two organizational factors are concerned, size and formalisation, both have a negative direct impact on learning capability and a negative indirect impact on the relationship between learning capability and firm’s performance. JEL Classification: L19